6-DOF force feedback control of robot-assisted bone fracture reduction system using double F/T sensors and adjustable admittances to protect bones against damage. (May 2016) - Kim, Woo Young; Ko, Seong Young; Park, Jong-Oh; Park, Sukho
Abstract: During a long bone fracture reduction surgery, assistant surgeons suffer from physical fatigue due to tension in the surrounding muscles of the patient's broken bones. To mitigate this physical workload, a positioning robot can be utilized by attracting and aligning a broken femur following a surgeon's command. However, the excessive force that the positioning robot exerts can cause damage to bone tissue or muscles of the patient. In this work, a force feedback scheme using double force-torque sensors and adjustable admittances is proposed to reduce the excessive forces exerted on broken bones by the positioning robot, as well as providing force feedback to the surgeon to feel the contact force between the bones. For this purpose, first a force feedback scheme is implemented to reduce the excessive force exerted on bone by moving the positioning robot toward the direction of larger force between the operational force and the scaled value of contact force. Second, it is shown that the proposed 1-DOF and 6-DOF force feedback are feasible by verifying that the operational force/torque command input and the environment contact forces are almost identical. Third, the force feedback scheme is shown to be capable of adjusting a force-scaling by adjusting a ratio of admittances of the operational force/torque command input to that of the environment contact force. At last, we also show that the performance of the force feedback is affected by the stiffness of the environment that includes medical bone fixture. As above, it is expected that the reliability and ease of bone fracture reduction robotic surgery will become possible by applying the force feedback scheme; it is also expected that secondary damage to bone tissue can be prevented by limiting the force of the positioning robot.